The Effect of COVID-19 Pandemic on Volatility Transmission Between the U.S. and Emerging Asia Stock Markets: A Case Study of Tiger Cub Economies - Ngoc, Mien Nguyen Thi (Animo Repository, 2021)
The globalization in financial markets has highlighted the importance of a clear understanding of volatility transmission among equity markets in different countries. This paper looks into the effect of the COVID-19 pandemic on the volatility transmission between the U.S. stock market and five emerging equity markets called Tiger Cub economies in Southeast Asia. As the result of the dynamic conditional correlation GARCH (DCC-GARCH), the U.S. stock market’s volatility links positively to these smaller economies’ volatilities, and these linkages become stronger during the pandemic. We also find evidence of statistically significant co-volatility across five Tiger Cub markets. Due to the increase in financial globalization over the last few decades, the finding has relevant implications for policymakers, international investors, and portfolio managers.